Player-Perceived Workplace Quality and Team Performance: Evidence from NFLPA Report Cards - Protte, Marius
This paper examines whether player-reported workplace quality is associated with team success in the National Football League (NFL). Using panel data for all 32 NFL teams across four seasons (2022-2025), we test whether NFLPA report card rankings-player evaluations of facilities, travel, medical support, coaching, and organizational environment-are related to regular season win percentage. Fixed effects models controlling for player quality, roster composition, injuries, coaching tenure, and past performance reveal a statistically significant within-team association between better player-reported workplace conditions and higher win percentages. However, this relationship does not persist when workplace quality is lagged, suggesting that player evaluations may partly reflect current team performance rather than predict future outcomes. These findings indicate that player evaluations of workplace quality are closely aligned with team success, highlighting the role of perception and short-run performance dynamics in a high-skill labor market setting.
Keywords: NFL team performance; NFLPA report cards; player satisfaction; organizational environment; non-pecuniary compensation

Human-Interactive Robot Learning: Definition, Challenges, and Recommendations - Baraka, Kim; Idrees, Ifrah; Faulkner, Taylor Kessler; Biyik, Erdem; Booth, Serena; Chetouani, Mohamed; Grollman, Daniel H.; Saran, Akanksha; Senft, Emmanuel; Tulli, Silvia; Vollmer, Anna-Lisa; Andriella, Antonio; et al. (Transactions on Human-Robot Interaction)
Robot learning from humans has been proposed and researched for several decades as a means to enable robots to learn new skills or adapt existing ones to new situations. Recent advances in artificial intelligence, including learning approaches like reinforcement learning and architectures like transformers and foundation models, combined with access to massive datasets, has created attractive opportunities to apply those data-hungry techniques to this problem. We argue that the focus on massive amounts of pre-collected data, and the resulting learning paradigm, where humans demonstrate and robots learn in isolation, is overshadowing a specialized area of work we term Human-Interactive-Robot-Learning (HIRL). This paradigm, wherein robots and humans interact during the learning process, is at the intersection of multiple fields (artificial intelligence, robotics, human-computer interaction, design and others) and holds unique promise. Using HIRL, robots can achieve greater sample efficiency (as humans can provide task knowledge through interaction), align with human preferences (as humans can guide the robot behavior towards their expectations), and explore more meaningfully and safely (as humans can utilize domain knowledge to guide learning and prevent catastrophic failures). This can result in robotic systems that can more quickly and easily adapt to new tasks in human environments. The objective of this paper is to provide a broad and consistent overview of HIRL research and to guide researchers toward understanding the scope of HIRL, and current open or underexplored challenges related to four themes — namely, human, robot learning, interaction, and broader context. The paper includes concrete use cases to illustrate the interaction between these challenges and inspire further research according to broad recommendations and a call for action for the growing HIRL community
Keywords: Robot learning; Interactive learning systems; Human-robot interaction; Human-in-the-loop machine learning; Teaching and learning

Bestimmt unbestimmt? - Eine quantitativ-explorative Studie zu Aufgabenprofilen von Fachkräften für das Multiprofessionelle Team (MPT) an inklusiven Gesamt-und Sekundarschulen in NRW. - Meusel, Sarah; Müller, Lukas; Jesuthasan, Jonitta (Zeitschrift für Inklusion)
Der Beitrag untersucht den Einsatz von Fachkräften für das Multiprofessionelle Team im Gemeinsamen Lernen (MPT). Diese meist sozialpädagogisch ausgebildeten Fachkräfte sind dezidiert für die Unterstützung der Inklusion an Grund-, Sekundar-und Gesamtschulen angestellt. Erste Befunde (Grüter et al.,2022) und ministeriale Aufgabenbeschreibung (Ministerium für Schule und Bildung des Landes Nordrhein-Westfalen [MSB NRW], 2022) deuten auf ein offenes, wenig definiertes Tätigkeitsspektrum hin. Mögliche Aufgabengebiete der MPT überschneiden sich mit denen der (sonderpädagogischen) Lehrkräfte, der Schulsozialarbeiter*innen und –im Hinblick auf die Unterstützung im Unterricht ohne Unterrichtsverantwortung –mit denen der Schulbegleitungen (Lübeck, 2019).Die Überlappungen legen nahe, dass auch für die MPT das „Zuständigkeitsdiffusitätsproblem“ (Kunze 2016, S.265) gilt und die multiprofessionelle Teamarbeit entsprechend beeinflusst. Da es bislang keine Daten darüber gibt, wie sich die Berufsrolle von MPT-Kräften in der Breite ausgestaltet, eruiert der Beitrag in einer quantitativen Studie ebendiese Frage. Zusätzlich werden die Fragenfokussiert, über welche Qualifikationen und Vorerfahrungen MPT-Kräfte verfügen und mit welchen Akteur*innen MPT-Kräfte in welcher Form kooperieren. Die Untersuchung bezieht sich auf den Einsatz von MPT an Gesamt-und Sekundarschulen in NRW. Insgesamt wurden 109 MPT-Kräfte in Form eines Online-Fragebogens befragt. Anhand der Ergebnisse konnte ein breites Einsatzgebiet mit vereinzelten Aufgabenschwerpunkten (v.a. im Bereich der sonderpädagogisch orientierten Kleingruppenförderung) der MPT-Kräfteidentifiziert werden. Schnittmengen zu Aufgabenschwerpunkten anderer Berufsgruppen werden unter Berücksichtigung der multiprofessionellen Kooperation hinsichtlich der Frage diskutiert, ob der Einsatz von MPT-Kräften inklusive Zielstellungen eher befördert oder im Sinne einer Deprofessionalisierung sonderpädagogischer Förderung eher entgegensteht.
Keywords: Deprofessionalisierung; Kooperation; Fachkräfte für das Multiprofessionelle Team(MPT); Aufgabenprofile in der inklusiven Schule

How Do Advanced Pre-Service Teachers Develop Congruence Theorems for Quadrilaterals? - Hoffmann, Max; Schlüter, Sarah (Proceedings of the Fifth Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2024, 10-14 June 2024))
In our paper, we present a study in which we investigate which strategies pre-service teachers (PSTs) use to find and, if necessary, reject possible candidates for congruence theorems for quadrilaterals. This study was conducted before the PTSs attended a university geometry course. In this way, statements about learning prerequisites can be made. For the study, we analyzed group discussions of PSTs to identify typical approaches and evaluate them from a mathematical perspective. The results can be considered for the further development of courses for PSTs and generate hypotheses for further research.
Keywords: Teachers’ and students’ practices at university level; Transition to; across and from university mathematics; Teaching and learning of specific topics in university mathematics; Congruence; Quadrilaterals

Métodos de la mediación de cultura en el entrenamiento práctico de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Revista Lengua y Cultura)
This study investigates the teaching methods that future teachers of German as a foreign language use in cultural mediation. Utilizing a qualitative and hermeneutic approach, it analyzes data from a teacher-training module of the International Master's in German as a Foreign/Second Language that Friedrich Schiller University Jena in Germany offers. Participants taught an online course to students from a Japanese university, which focused on cultural learning. Within the teacher training module, the participants discussed their lesson plans, conducted classes, and subsequently reflected on their teaching practices by exploring and critiquing the practical application of their teaching skills. The analysis, which was conducted using qualitative evaluative content analysis following Kuckartz's (2018) approach, revealed a preference for distributive/instructive methods, with some recognition of interactive and collaborative methods. A tendency towards both repetitive and reflective practices was evident, with a predominant focus on content that was specific to a supposed target culture rather than intercultural or transcultural content. The study highlights the need to balance knowledge transmission with the development of critical and reflective skills in cultural mediation. It emphasizes the importance of incorporating collaborative and interactive methods, which promote a critical attitude that is necessary in language teachers and learners. In conclusion, this study advocates adaptive and reflective teaching as an essential component in the training of future language teachers in globalized contexts.
Keywords: cultural mediation; teacher training; foreign language teaching; teaching methods; teaching practice

Student Teachers ’ Knowledge of Congruence before a University Course on Geometry - Hoffmann, Max; Biehler, Rolf (Proceedings of the Fourth Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2022, 19-22 October 2022))
Keywords: Teaching and learning of specific topics in university mathematics; Transition to; across and from university mathematics; Student Teachers; Geometry; Congruence; Double Discontinuity.

Research Approaches on Workplace Learning
The volume comprises a variety of research approaches that seek to explore and understand employees’ learning and development through and for work. Working life reveals challenges through technological, economic and societal development that can only rudimentarily be addressed by formal education and training. Workplace learning becomes more and more important for employees and enterprises to successfully cope with these challenges. Workplace learning is a steadily growing field of educational research but it lacks so far a scholastic canon – there is rather a diversity of research approaches. This volume reflects this diversity by bringing together researchers from different countries and different theoretical backgrounds, presenting their current research on topics that all are relevant for understanding presages, processes and outcomes of workplace learning. Hence, this volume is of relevance for researchers as well as practitioners in the field and policy makers.
Keywords: tivesTeam learningTeam climateSocial influences on team learningKnowledge construction in teamsLearning cultureAcknowledgement of competencesTechnology and professional learningCreation of a learning eco-systemDiversity as a challenge for organisationsHigher education as preparation for WPLSocial support in networks and professional learningvocational and professional education

Von der Not zur Tugend!? - Caruso, Carina; Bruns, Marike; Harteis, Christian (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s) Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Der Begriff der „Zwangsdigitalisierung“ beschreibt, dass als eine Folge der Corona-Pandemie Präsenzformate durch digital gestützte Settings ersetzt werden sowie Alter- nativen zur Kommunikation und für das gemeinsame Arbeiten und Lernen in Präsenz gefunden werden mussten. Digital gestützte Lehr-Lernsettings scheinen seit dem ersten Lockdown sowohl an Schulen als auch an Hochschulen eine Möglichkeit dafür darzustellen, die Lern- und Entwicklungsprozesse (z. B. von Schülerinnen und Schülern, angehenden Lehrkräften) trotz physischer Distanz weiterzuführen. In diesem Beitrag werden die mit der Zwangsdigitalisierung an den Hochschulen verbundenen Chancen und Grenzen für die Entwicklung digitalisierungsbezogener Kompetenzen angehender Lehrkräfte herausgearbeitet. Dabei richtet sich der Blick auf den Wert von Erfahrungen für Lernen und Entwicklung. Zudem wird, gemäß der den Angebots-Nutzungs-Modellen inhärenten Logik einer „Wirkkette“, Bezug genommen auf Perspektiven von Studierenden, deren prospektiven Schülerinnen und Schülern sowie von Dozierenden.
Keywords: Hochschullehre; Lehrer:innenausbildung; Medienkompetenz / teacher education; teaching at university; media literacy

Die Wirksamkeit von Lernzielen für Studienleistungen – eine experimentelle Studie - Auer, Thorsten Fabian (die hochschullehre)
According to the German Rectors’ Conference (HRK), German higher education teaching fails to meet the demand to integrate competence-oriented learning objectives. Despite a wide-ranging debate on the use of learning objectives, empirical research on their effectiveness is scarce. The present study uses the features of digital teaching platforms to investigate the perception and effectiveness of learning objectives applying a randomised controlled experiment followed by a survey in a course for undergraduate economics students (N = 30). Controlling group preconditions and the treatment effect allows to draw conclusions about the different learning outcomes of the student groups. The specification of behaviour-oriented learning objectives in the online course system leads to significantly better performance in the treatment group. A stronger perception of the learning objectives in the treatment group supports this effect that remains significant in a regression analysis. Thus, the study provides an empirical justification to integrate learning objectives in university teaching.
Keywords: learning objectives; academic performance; perception; teaching methods; experiment

Einfluss der Berufserfahrung von Multiplikatorinnen und Multiplikatoren auf die Wirksamkeit von Fortbildungsmaßnahmen zur frühen mathematischen Bildung. Zeitschrift Für Erziehungswissenschaft - Hagena, Maike; Bruns, Julia; Gasteiger, Hedwig (Zeitschrift für Erziehungswissenschaft)
Teachers expect facilitators to have own teaching experience as a teacher in order to be able to carry out effective teacher professional development programs. As part of the project EmMa(M), it is investigated, to which extent the teaching experience of facilitators influences the development of early childhood teachers' (n = 83) mathematical pedagogical content knowledge (MPCK) and early childhood teachers' enjoyment of mathematics in the context of a teacher professional development program. It turns out that the teaching experience of the facilitators has no influence on the development of early childhood teachers' MPCK, but favors the development of early childhood teachers' enjoyment of mathematics. Controlling for this increased enjoyment an influence of teaching experience on the development of early childhood teachers' MPCK emerges, but in favor of the participating facilitators who have no teaching experience but have a university degree.
Keywords: Facilitator professional development; Early childhood teachers; Teaching; experience; Early mathematics education

Digitale Räume geben und nehmen: Unterrichtsinteraktion in DSH-Kursen während der COVID-19-Pandemie - Drumm, Sandra; Müller, Mareike; Stenzel, Nadja (Informationen Deutsch als Fremdsprache)
Das Auftreten der COVID-19-Pandemie stellt Fremdsprachenkurse vielerorts vor Herausforderungen. Unter Zuhilfenahme diverser digitaler Tools werden nicht nur Lernmaterialien online geteilt, sondern auch die Interaktion zwischen Lehrenden und Lernenden sowie der Lernenden untereinander in den virtuellen Raum verlagert. Qualitative Interviews mit den Beteiligten erfassen, wie diese mit den Herausforderungen videogestützten Sprachunterrichts umgehen und welche Strategien sie wählen, um Sprachenlernen zu ermöglichen. Die Ergebnisse zeigen auf, wo seitens der Kursorganisation und -durchführung Handlungsbedarf besteht. ----- The rise of the COVID-19 pandemic challenges the teaching and learning of foreign languages at many institutions. The implementation of various digital tools aids not only the online sharing of learning materials, but also shifts teacher-learner and learner-learner interaction to the virtual space. Via qualitative interviews, this study examines how both teachers and learners handle the challenges of language instruction based on videoconferences, and what strategies they employ to enable language learning. The results highlight areas in need of improvement in terms of course organization and facilitation.
Keywords: German language courses at university; interaction; digital space; language learning/teaching via videoconference

Collaboration Is the Key – The Role of Special Educators in Inclusive Schools in Germany - Neumann, Phillip; Lütje-Klose, Birgit (International Perspectives on Inclusive Education)
Inclusive education is about creating beneficial environments for all students (Booth & Ainscow, 2011). Within Germany, the role of special education within inclusive schools has been widely discussed in Germany (Powell et al., 2016). Educators worldwide consider collaborative teaching between special educators and general educators to be a fundamental precondition for inclusive education (Hoppey & McLeskey, 2014). The history of the German school system, however, is characterized by a rigorous division of special and regular schools that is reflective of broad divisions in teacher education. Since the ratification of the Convention on the Rights of Persons with Disabilities (CRPD) in Germany in 2009, more students with special educational needs, as well as special educators, have begun to attend and work in inclusive schools. While cooperation between general and special educators is a key to the development of inclusive schools, many teachers report that responsibilities are divided between special and general teachers, while various challenges exist regarding cooperation (Urban & Lütje-Klose, 2014). Nevertheless, dysfunctional cooperation can foster mechanisms of separation and exclusion even in “inclusive” settings (Idel et al., 2019). The present chapter offers a reflection on the different roles of special educators and the current state of research on interdisciplinary and multi professional cooperation in inclusive schools in Germany. It also provides a discussion of relevant implications for the development of inclusive schools and teacher training.
Keywords: Kooperation; Inklusion; Sonderpädagogik; Schulentwicklung; Inclusion; Cooperation; Collaboration; Team-Teaching; International; Germany

The Concept of a Digital Twin and Its Potential for Learning Organizations - Berisha-Gawlowski, Angelina; Caruso, Carina; Harteis, Christian (Digital Transformation of Learning Organizations)
The digital transformation of organizations in the industrial sector is primarily driven by the opportunity to increase productivity while simultaneously reducing costs through integration into a cyber-physical system. One way to fully tap the potential of a cyber-physical system is the concept of the digital twin, i.e., the real-time digital representation of machines and resources involved – including human resources. The vision of representing humans by digital twins primarily aims at increasing economic benefits. The digital twin of a human, however, cannot be designed in a similar way to that of a machine. The human digital twin shall rather enable humans to act within the cyber-physical system. It therefore offers humans a power of control and the opportunity to provide feedback. The concept of the digital twin is still in its infancy and raises many questions in particular from an educational perspective. The contribution aims at answering the following questions and refers to the example of team learning: Which and how much data should and may the digital twin contain in order to support humans in their learning? To what extent will humans be able to control and design their own learning? How may skills, experiences, and social interactions of humans be represented in the digital twin; their growth and further development, respectively? With cyber-physical systems transcending corporate, national, and legal boundaries, what learning culture will be the frame of reference for the involved organizations?
Keywords: Digital twin; Learning organization; Change; Team learning; Professional development

The Debate on student evaluations of teaching: global convergence confronts higher education traditions - Pineda, Pedro; Steinhardt, Isabel (Teaching in Higher Education)
Through co-occurrence analysis of 1139 documents (1964-2018) we identified trends in the discussions about the implementation of student teaching evaluation (SET). We found that: (1) Attention to SET originated in the US in the 1970s, spreading to German-speaking countries in the mid-1990s and continuing in China and Latin America in the early 2000s. (2) SET is commonly viewed as a control tool deserving methodological improvement, while bias is debated in the US. We also found local trajectories: (3) Whereas in the US and Latin America SET is primarily seen as a management tool, German-speaking and Chinese authors reflect more on improving teaching. Chinese scholars consider SET a valid instrument for state control associated with artificial intelligence. Also, (4) SET is commonly used in medical education in the US and the German-speaking region and in physical education in China. We conclude that SET is discussed cross-nationally but affected by national path dependencies.
Keywords: academic discourse; bibliometric review; quality assurance; student evaluation of teaching; teaching evaluation

Data Science und Big Data in der beruflichen Bildung – Konzeption und Erprobung eines Projektkurses für die Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael (Sammelband der 27. Fachtagung der BAG Berufliche Bildung)
Die Themen „Big Data“, „Künstliche Intelligenz und „Data Science“ werden seit einiger Zeit nicht nur in der breiten Öffentlichkeit kontrovers diskutiert, sondern stellen für die Ausbildung in den IT- und IT-nahen Berufen schon heute neue Herausforderungen dar, die in Zukunft durch die gesellschaftliche und technologische Weiterentwicklung hin zu einer Datengesellschaft noch größer werden. An dieser Stelle stellt sich die Frage, welche Aspekte dieses großen Themenkomplexes für Schule und Ausbildung von Wichtigkeit sind und wie diese Themen sinnstiftend und gewinnbringend in die informatische Ausbildung in verschiedenen Bildungsgängen integriert werden können. Im Rahmen des von uns im Jahr 2017 organisierten Symposiums zum Thema „Data Science“ wurden für die Bildung relevante Aspekte erörtert, wodurch als Kernelemente für den Unterricht Algorithmen der Künstlichen Intelligenz und ihre Anwendung in Industrie und Gesellschaft, Explorationen von Big Data sowie der Umgang mit eigenen Daten in sozialen Netzwerken herausgearbeitet wurden. Ziel ist, aus diesen Themenbereichen sowohl ein umfassendes Curriculum als auch Module für verschiedene Unterrichtsszenarien zu entwickeln und zu erproben. Durch diese Materialien soll es Lehrkräften aus der Informatik, Mathematik oder Technik ermöglicht werden, diese Themen auf Basis des Curriculums und der erprobten Unterrichtskonzepte selbst zu unterrichten. Hierfür wurde im Rahmen des Projekts ProDaBi (Projekt Data Science und Big Data in der Schule, https://www.prodabi.de), initiiert von der Telekom Stiftung, ein experimenteller Projektkurs entwickelt, den wir mit Schüler:innen der Sekundarstufe II an der Universität Paderborn im Schuljahr 2018/19 durchführten. Dieser Kurs enthält neben einem Modul zur Exploration von Big Data und einem weiteren Modul zum Maschinellen Lernen als Teil der Künstlichen Intelligenz auch eine Projektphase, die es in Zusammenarbeit mit lokalen Unternehmen den Schüler:innen ermöglicht, das Erlernte in ein reales Data Science-Projekt einzubringen. Aus den Erfahrungen dieses Projektkurses sowie den parallel durchgeführten Erprobungen einzelner Bausteine auch mit beruflichen Schulen werden ab dem Schuljahr 2019/20 die hierfür verwendeten Materialien weiterentwickelt und weiteren Kooperationspartnern zur Erprobung zur Verfügung gestellt. Damit wurden zum Ende des Projekts nicht nur vollständige Unterrichtsmaterialien, sondern auch ein umfassendes Curriculum entwickelt.
Keywords: Berufsbildung; vocational education; Ausbildung; training; berufliche Weiterbildung; advanced vocational education; Digitalisierung; digitalization; Unterricht; teaching; Lehrmethode; teaching method; Interdisziplinarität; interdisciplinarity; Fachdidaktik; subject didactics; Curriculum; curriculum; gewerblich-technischer Beruf; vocational/technical occupation; Fachkraft; specialist; Qualifikationsanforderungen; qualification requirements; Kompetenz; competence; Lehrerbildung; teacher training; Bundesrepublik Deutschland; Federal Republic of Germany

Squaring the circle: Business model teaching in large classroom settings - Szopinski, Daniel (Journal of Business Models)
Business model innovation is typically taught in small seminars at universities. Teaching this intrinsically task-oriented subject to a large number of students is a challenge. In this paper we address this challenge by proposing an experiential and interactive approach to teaching business models in a large classroom setting.
Keywords: Business model teaching; peer assessment; experiential learning

Understanding Artificial Intelligence – A Project for the Development of Comprehensive Teaching Material - Schlichtig, Michael; Opel, Simone Anna; Budde, Lea; Schulte, Carsten (ISSEP 2019 - 12th International conference on informatics in schools: Situation, evaluation and perspectives, Local Proceedings)
Artificial intelligence (AI) has the potential for far-reaching – in our opinion – irreversible changes. They range from effects on the individual and society to new societal and social issues. The question arises as to how students can learn the basic functioning of AI systems, what areas of life and society are affected by these and – most important – how their own lives are affected by these changes. Therefore, we are developing and evaluating school materials for the German ”Science Year AI”. It can be used for students of all school types from the seventh grade upwards and will be distributed to about 2000 schools in autumn with the support of the Federal Ministry of Education and Research. The material deals with the following aspects of AI: Discussing everyday experiences with AI, how does machine learning work, historical development of AI concepts, difference between man and machine, future distribution of roles between man and machine, in which AI world do we want to live and how much AI would we like to have in our lives. Through an accompanying evaluation, high quality of the technical content and didactic preparation is achieved in order to guarantee the long-term applicability in the teaching context in the different age groups and school types. In this paper, we describe the current state of the material development, the challenges arising, and the results of tests with different classes to date. We also present first ideas for evaluating the results.
Keywords: Artificial Intelligence; Machine Learning; Teaching Material; Societal Aspects; Ethics. Social Aspects; Science Year; Simulation Game

Evaluating Innovative Measures in University Mathematics – The Case of Affective Outcomes in a Lecture focused on Problem-Solving - Kuklinski, Christiane; Leis, Elena; Liebendörfer, Michael; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Neuhaus, Silke; Schaper, Niclas; Schürmann, Mirko (Proceedings of the Second Conference of the International Network for Didactic Research in University Mathematics (INDRUM 2018, 5-7 April 2018))
The transition from high school to university mathematics has proven to be difficult for many students but especially for pre-service secondary teachers. To support these students at mastering this transition, various universities have introduced support measures of various kinds. The WiGeMath project developed a taxonomy that makes it possible to describe and compare these measures concerning their goals as well as their frame characteristics. We will exemplify the use of the taxonomy in the description of one specific innovative measure that was part of the WiGeMath evaluations. Moreover, we will present first results concerning the goal-fulfilment of this measure concerning affective characteristics of the student cohort and their predominant beliefs.
Keywords: Beliefs.; Motivational developments; Novel approaches to teaching; Teacher education; Transition to and across university mathematics

Apps in der musikpädagogischen Praxis. Eine explorative Studie zur kommunikativen Konstruktion von mobilen Technologien im schulischen Nachmittagsbereich - Godau, Marc (Musikpädagogik und Kulturwissenschaft)
This article provides an insight into a qualitative research project concerning music educational practices with mobile music technologies. Based on social systems theory, this grounded-theory study observes how groups in two extracurricular music classes construct different technologies (e. g., iPads, mixers, ear phones) within the emergence of (reflexive) expectations as social structures. The results reveal five categories of technologies: technology as an instrument-toy-alternator that supports motivation, as a medium for knowledge and learning, as an adjusting device used for socio-aesthetic decision making, as a didactical tool for task-based situations, and as an isolator for inner differentiation by focusing aural perception. (DIPF/Orig.)
Keywords: Musical education; Musikpädagogik; Musikunterricht; Deployment of media; Medien; Medieneinsatz; Mobile Computing; Music lessons; Qualitative Forschung; Qualitative research; Teaching of music; Use of media

Wie kommen die Dinge in den Musikunterricht? Zur Materialität musikpädagogischer Praxis am Beispiel divergierender Orientierungen im Kontext unterrichtsbezogenen Handelns angehender Lehrkräfte - Godau, Marc (Soziale Aspekte des Musiklernens)
During the past decade, there has been an increase of pedagogical research under conditions of posthuman theories, such as the Actor Network Theory or post-phenomenology. Yet, there has not been much research on the materiality of music pedagogical practices. This article introduces an ongoing grounded-theory study on the role of things (e.g., music instruments, black board, or digital devices) within the music classroom. Results from the analysis of group discussions and interviews with student teachers show tensions between personal preferences, school conventions, and material conventions within the process of introducing things into the classroom. (DIPF/Orig.)
Keywords: Interview; Lehrer; Musical education; Musikpädagogik; Musikunterricht; Teacher; Music lessons; Qualitative Forschung; Qualitative research; Teaching of music; Object; Objekt; Ding; Handlung; Practice; Praxis; Probationary teacher training; Referendariat